Improving Students’ Speaking Achievement by Using Storytelling Technique - Novalina Sembiring; Fiber Y.A. Ginting (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This study was aimed to improve the students’ speaking achievement by using storytelling technique. The subject of the study was the eight grade students of Public Junior High School 22 Medan in academic year 2018/2019. This study was conducted by applying Classrom Action Research (CAR), which had been conducted in two cycles and each cycle consisted of three meetings. The instruments of collecting data were quantitative data (speaking test) and qualitative data (observation checklist and field notes). The result of the test shows that the mean score of pre test is 40, formative test is 46.34, and post test is 62.89. The percentage of the students’ means score improve from pre test to post test 57.2%. The result of observation checklist and field notes showed that the students were interested in teaching and learning English especially speaking skill by using storytelling technique. These indicated that there was a significant improvement of the students’ speaking achievement by using storytelling technique.